(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
We propose a study of judicial practice in a society undergoing mediatization. We noticed that the way the procedural actors behave, in the context where the institutions are crossed by mediatization logics, tensions the instituted. Social experimentation pressures the norm (and fundamental rights). In this context, we consider it productive to make methodological reflections on how to research within the legal-communicational interface. After contextualizing the present moment (judicial activism) mobilizing the concept of mediatization, we used the concept of interactional devices to investigate the two empirical objects selected for the study of cases. The first, the dispute over the position of the cameras in the testimony of former President Lula before the ex-judge Sérgio Moro. The second, the debate about the meaning of being a journalist, mediated by the judicial practice in the judicial process of blogger Eduardo Guimarães. In both cases we notice the phenomena of judicial activism and judicialization becoming more complex by mediatization. We perceive the fundamental right of due process and the constitutional guarantee to the secrecy of the source being strained by experiments that go beyond canonical legal logics, putting at risk indispensable rights to the Democratic State of Law.